Recommendation CM/Rec(2025)6 on Qualifications and Linguistic Competences of Refugees in Europe (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The Committee of Ministers, composed of the Ministers of Foreign Affairs of the 46 member states that make of the Council of Europe, is responsible for issuing recommendations that shape member state’s practices. Adopted by the Committee of Ministers of the Council of Europe in July 2025, Recommendation CM/Rec(2025)6 provides guidance to member states on recognizing and valuing the qualifications and language competences of refugees and displaced persons. The recommendation emphasizes fair, transparent, and inclusive procedures for credential recognition, even in cases where full documentation is unavailable. It also highlights the importance of supporting refugees’ linguistic integration to enhance access to education, training, and employment. The document outlines policy measures and cooperative approaches that member states can adopt to strengthen recognition systems and promote equitable participation in European societies.  Citation Council of Europe. (2025, July 9). Recommendation CM/Rec(2025)6 of the Committee of Ministers to member States on qualifications and linguistic competences of refugees in Europe. https://search.coe.int/cm?i=091259488027d22e